Multiple conserved regulatory elements with overlapping functions determine Sox10 expression in mouse embryogenesis. - Wegner, Michael; et al. (Nucleic Acids Research, 2007)
Expression and function of the transcription factor Sox10 is predominant in neural crest cells, its derivatives and in oligodendrocytes. To understand how Sox10 expression is regulated during development, we analysed the potential of evolutionary conserved non-coding sequences in the Sox10 genomic region to function as enhancers. By linking these sequences to a β-galactosidase marker gene under the control of a minimal promoter, five regulatory regions were identified that direct marker gene expression in transgenic mice to Sox10 expressing cell types and tissues in a defined temporal pattern. These possible enhancers of the Sox10 gene mediate Sox10 expression in the otic vesicle, in oligodendrocytes and in several neural crest derivatives including the developing peripheral nervous system and the adrenal gland. They furthermore exhibit overlapping activities and share binding sites for Sox, Lef/Tcf, Pax and AP2 transcription factors. This may explain high level and robustness of Sox10 expression during embryonic development. © 2007 The Author(s).
UnivIS-Import:2015-03-09:Pub.2007.med.IB.LPCIPDBI.multip